THEORIES OF ECONOMICS AND THE PHILOSOPHY OF ALTRUISM IN “TWINNING” THE EGYPTIAN TOURISM AND TEXTILE INDUSTRIES - ELNASHAR, Elsayed Ahmed; LIUBOKHYNETS, Larysa; TANASIIENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Theories of economics and the philosophy of altruism in “twinning” this paper studies the endogenous formation of interfiling altruism. The theory suggests that incentive to foster tourism and textile industries is positively related to efficiency gains from more human capital investment in the more gifted tourism and textile industries. The empirical analyses explore the plausibly exogenous within-twin difference in for the development of Matrouh governorate, Egypt, consistent with the theory, the estimation results show that a larger difference in tourism and textile industries. Leads to more intensive you win-to to be-win practice to tourism and textile industries and that when such practice is more intensive, the heavier tourism and textile industries obtains more investment relative to the other tourism and others industries as the philosophy of altruism in “twinning”.
Keywords: altruism; twinning; Egyptian tourism; textile industries